PENJASORKES LEARNING AS A MEANS OF CHARACTER BUILDING (A REFLECTION OF PENJASORKES TEACHING-LEARNING PROCESSES AT SMPN KOTA SURAKARTA - Riyadi, Slamet; Kristiyanto, Agus (Universitas Negeri Semarang, 2016)
This study aimed to describe the planning and action processes of health, sports, and physical education (henceforth penjasorkes) at junior high school as an effort of implanting character values. This research was conducted at four Public Junior High Schools (henceforth SMPN) in the Municipality of Surakarta, Central Java. The subjects of the study were 30 penjasorkes teachers, 117 respective students, and documents of teaching-learning devices. This was a descriptive research study. The techniques employed for collecting data were observation, interview, questionnaire, and documentary study. The results of this study show that most teachers did not have any teaching-learning plan which matched the school condition. Teachers prepared their lesson plan just to fulfill the requirements of teaching-learning administration. The penjasorkes teaching-learning processes that had been carried out by the teachers so far stressed more on the teachers’ skill and performance. They mostly applied authoritarian approaches supported by some standard learning facilities. The character values implanted through this typical approach developed without any learning modification, it merely stressed on disciplinary trait as the main value. Other character values were developed neither through habit nor deep intervention during the teaching-learning processes.